2011
DOI: 10.2214/ajr.10.5041
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy Dual-Source CT With Additional Spectral Filtration Can Improve the Differentiation of Non–Uric Acid Renal Stones: An Ex Vivo Phantom Study

Abstract: Purpose To determine the ex vivo ability of dual-energy, dual-source computed tomography (DE-DSCT) with additional tin filtration to differentiate between five groups of human renal stone types. Methods Forty-three renal stones of ten types were categorized into five primary groups based on effective atomic numbers, which were calculated as the weighted average of the atomic numbers of constituent atoms. Stones were embedded in porcine kidneys and placed in a 35cm water phantom. DE-DSCT scans were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 34 publications
3
91
0
2
Order By: Relevance
“…Further characterization of calcium calculi remains even more difficult because of overlap in their attenuation values (13,16). With the introduction of second-generation dual-source DECT with added tin filtration, a few in vitro studies have shown that further characterization of calcium calculi may be possible (17)(18)(19)(20) whereas a few others have concluded otherwise (21).…”
Section: Introductionmentioning
confidence: 99%
“…Further characterization of calcium calculi remains even more difficult because of overlap in their attenuation values (13,16). With the introduction of second-generation dual-source DECT with added tin filtration, a few in vitro studies have shown that further characterization of calcium calculi may be possible (17)(18)(19)(20) whereas a few others have concluded otherwise (21).…”
Section: Introductionmentioning
confidence: 99%
“…11 Qu et al also demonstrated better separation of different types of stones ex vivo as well. 12 The characterization of various stone is based on the dual energy ratio and x ray attenuation or HU.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Conventional US is the first-line modality for evaluating the urinary tract. However, sound beam attenuation in obesity and superposition of colonic gas may prevent optimal visualization for diagnosis.…”
Section: Discussionmentioning
confidence: 99%